Sex Differences in the Excess Risk of Cardiovascular Diseases Associated with Type 2 Diabetes: Potential Explanations and Clinical Implications - Peters, S.; Huxley, Rachel; Sattar, N.; Woodward, M. (2015)
Strong evidence suggests that type 2 diabetes confers a stronger excess risk of cardiovascular diseases in women than in men; with women having a 27 % higher relative risk of stroke and a 44 % higher relative risk of coronary heart disease compared with men. The mechanisms that underpin these sex differences in the associations between diabetes and cardiovascular disease risk are not fully understood. Some of the excess risk may be the result of a sex disparity in the management and treatment of diabetes, to the detriment of women. However, accruing evidence suggests that real biological differences between men and women underpin the excess risk of diabetes-related cardiovascular risk in women such that there is a greater decline in risk factor status in women than in men in the transition from normoglycemia to overt diabetes. This greater risk factor decline appears to be associated with women having to put on more weight than men, and thus attain a higher body mass index, to develop diabetes. Further studies addressing the mechanisms responsible for sex differences in the excess risk of cardiovascular diseases associated with diabetes are needed to improve the prevention and management of diabetes in clinical practise.